The relationship between serum malondialdehyde levels and severity of acne vulgaris on male - Kristiana Etnawati, Aprilina Dwi Sulistyowati, Dwi Retno Adiwinarni, (Universitas Gadjah Mada, 2014)
Acne vulgaris is a multifactorial disorder characterized by seborrhea, microcomedones, comedones,papules, pustules, nodules and possibly scarring. The pathogenesis of acne is not completelyunderstood. Recent studies reported the possible role of reactive oxygen spesies (ROS) especiallylipid peroxides in mediating acne inflammation. Malondialdehyde (MDA) is one of the final productsof the lipid peroxidation that commonly used as a lipid peroxidation marker. This study was conductedto evaluate the correlation between serum MDA levels and severity of acne on male patients. A total60 patients with acne who attended in Polyclinic of Department of Dermatology and Venereology,Dr Sardjito General Hospital and met the inclusion and exclusion were involved in the study. Thepatients were then classified using combined acne severity classification method into three group asmild, modrate and severe acnes. Blood sample were then taken from all subjects and serum MDAlevels were determined spectrophotometer. The mean serum MDA levels of severe acne group(1.85 ± 0.368 μmol/L) were significantly higher than that moderate acne group (0.79 ± 0.159μmol/L) (p = 0.000) and that mild acne group (0.52 ± 0.239 μmol/L) (p = 0.000). Moreover, themean MDA levels of moderate acne group were also significantly higher than that mild acne group(p = 0.002). Significantly positive correlation was observed between serum MDA levels and acnelesions total count (r = 0.714; p = 0.000). It can be concluded, there is positive relationshipbetween serum MDA levels and severity of acne vulgaris on male patients.